ANALYSIS OF SERVICE QUALITY AND LOCATION ON PATIENT SATISFACTION AT BHAKTI KOPETRI CLINIC - Hasna Imtitsal Imaning Putri; Puji Isyanto; Neni Sumarni (Journal Of Resource Management, Economics And Business, 2024)
Purpose: This research aims to examine the influence of service quality and location on patient satisfaction at the Bhakti Kopetri Clinic. It seeks to understand how these factors contribute to the overall patient experience in the context of rapidly developing clinics in Indonesia. Research Methodology: The study employs a descriptive and verification approach, utilizing a classic assumption test that includes normality, multicollinearity, heteroscedasticity tests, as well as multiple linear regression, t-tests, and F-tests. A sample of 96 patients who had received treatment at the Bhakti Kopetri Clinic was selected using purposive sampling techniques. Results: The findings indicate that the service quality variable has a positive and significant effect on patient satisfaction. Similarly, the location also positively and significantly impacts patient satisfaction. Furthermore, both service quality and location together have a simultaneous and significant effect on patient satisfaction. Limitations: The research is limited to a single clinic and may not be generalizable to other healthcare facilities. Additionally, the sample size, while adequate, could be expanded for future studies to enhance reliability. Contribution: This study contributes to the understanding of how service quality and location influence patient satisfaction in healthcare settings, providing insights that can help clinics improve their services and better meet patient expectations.